A high reliability physically unclonable function based on multiple tunable ring oscillator. (November 2021) - Zhang, Yuan; Liang, Huaguo; Yao, Liang; Yi, Maoxiang; Huang, Zhengfeng; Lu, Yingchun
Abstract: Physical unclonable functions (PUF) is a hardware security primitive which can generate unique chip identification and has a broad application prospect. However, because the reliability of PUF is easily affected by the complex external environment, the security of device authentication is threatened. In this paper, a multi tunable ring oscillator structure is designed, which can change the transmission path of the oscillation signal and the internal delay of each device at the same time. In this way, the delay complexity of entropy source structure can be maximized, and more authentication key data can be generated by using a small amount of hardware resources. On this basis, a prediction test screening system is proposed. Through the preselection system, the proposed PUF is tested at low temperature and high temperature for a short time. The threshold used to filter responses can be set more accurately to extract the high deviation response, which can greatly improve the reliability of PUF and make equipment certification more secure. The experimental results show that the designed PUF can achieve 49.52% uniformity and 49.17% uniqueness, which is very close to the ideal value. Moreover, it can maintain high reliability in a wide range of −40–100 °C and 0.8–1.2 V, indicating an encouraging effectiveness and reliability.